Optimasi Variasi Media Pendingin Dari Minyak Nabati Terhadap Kekasaran Permukaan Baja AISI 1045 Pada Proses Bubut CNC Menggunakan Metode Taguchi - Farehan, Ander; Husman, Husman; Novitasari, Novitasari (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
Along with customer demand, the manufacturing industry must improve the quality of its products. In addition to product quality, environmental, safety, and health and welfare considerations also have a significant impact on the manufacturing business. One of the products of the manufacturing industry is a shaft which in its manufacture refers to the level of surface roughness. To minimize the surface roughness of the workpiece as a result of CNC lathe machining, coolant can be used. One of them is using coolant from vegetable oil. Vegetable oil is known as an ecologically acceptable and safe cooling medium for use in manufacturing operations. So a study was conducted to determine the surface roughness value of the workpiece (AISI 1045 steel) using 2 types of vegetable oil as a cooling medium (coconut oil and palm oil). Taguchi experimental design was used in this study. Based on the measurement results, the surface roughness value of AISI 1045 steel with palm oil coolant is 1.614 m, and coconut oil is 1.554 m. The coconut oil coolant type can optimize the minimum AISI 1045 steel surface roughness value with a value of 1,554 m at a cutting speed of 1273 rpm, a depth of cut of 0.50 mm, and a cutting motion of 0.16 mm/put.